Trends in hospital presentations following analytically confirmed synthetic cannabinoid receptor agonist exposure before and after implementation of the 2016 UK Psychoactive Substances Act. (19th June 2022) - Craft, Sam; Dunn, Michael; Vidler, Dan; Officer, Jane; Blagbrough, Ian S.; Pudney, Christopher R.; Henderson, Graeme; Abouzeid, Ahmed; Dargan, Paul I.; Eddleston, Michael; Cooper, Jamie; Hill, Simon L.; et al.
Abstract: Background and aims: The United Kingdom (UK) Psychoactive Substances Act (PSA), implemented on the 26 th  May 2016, made the production, supply and sale of all non‐exempted psychoactive substances illegal. The aim of this study was to measure trends in hospital presentations for severe toxicity following analytically confirmed synthetic cannabinoid receptor agonist (SCRA) exposure before and after implementation of the PSA. Design: Observational study. Setting: Thirty‐four hospitals across the UK participating in the Identification of Novel Psychoactive Substances (IONA) study. Participants: A total of 627 (79.9% male) consenting individuals who presented to participating hospitals between July 2015 and December 2019 with severe acute toxicity and suspected novel psychoactive substances exposure. Measurements: Toxicological analyses of patient samples were conducted using liquid‐chromatography tandem mass‐spectrometry. Time‐series analysis was conducted on the monthly number of patients with and without analytically confirmed SCRA exposure using Poisson segmented regression. Findings: SCRAs were detected in 35.7% ( n =  224) of patients. After adjusting for seasonality and the number of active sites, models showed no clear evidence of an upward or downward trend in the number of SCRA exposure cases in the period before (incidence rate ratio [IRR], 1.12; 95% CI, 0.99–1.26; P  = 0.068) or after (IRR, 0.97; 95% CI, 0.94–1.01; P  = 0.202) the implementation of the PSA. There was also no clear evidence of an upward or downward trend in non‐SCRA exposure cases before (IRR, 1.12; 95% CI, 0.98–1.27; P  = 0.105) or after (IRR, 1.01; 95% CI, 0.98–1.04; P  = 0.478) implementation of the PSA. Conclusions: There is no clear evidence of an upward or downward trend in the number of patients presenting to UK hospitals with severe acute toxicity following analytically confirmed synthetic cannabinoid receptor agonist exposure since the implementation of the Psychoactive Substances Act.